Pemanfaatan Media Sosial sebagai Regenerasi Musik Tradisional Minangkabau kepada Generasi Muda Melalui Content Creator Musik Tradisi - M. Aldhe Vishal; Alrizka Hairi Dilfa (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
This study aims to analyze the use of social media as a means of regenerating Minangkabau traditional music among the younger generation through the role of traditional music content creators. The background of this research stems from the declining interest of young people in traditional music due to the dominance of popular culture and modernization. However, the emergence of content creators who utilize digital platforms such as YouTube, TikTok, and Instagram has opened new opportunities for the preservation of traditional music. This study employs a descriptive qualitative approach with data collected through in-depth interviews, observations, and documentation of several Minangkabau music content creators. The results show that social media plays a crucial role in the regeneration process of traditional music through three main functions: information (promotion), interaction, and motivation. By presenting engaging visuals, combining traditional music with modern elements, and encouraging interactive audience participation, social media effectively attracts young people to learn and appreciate traditional music. In addition, regeneration is the process of inheriting cultural values ​​through efforts to maintain the sustainability of performing arts by adapting the presentation methods and performance spaces to suit the times, so that traditional arts remain acceptable to modern society.